SALAM DAN UNGKAPAN PERPISAHAN DALAM BAHASA INGGRIS DAN BAHASA KOREA (SUATU ANALISIS KONTRASTIF) - MANUA, MARIEL A. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT Â The title of this research is â€œ Salam dan Ungkapan Perpisahan dalam Bahasa Inggris dan Bahasa Korea : Contrastive analysisâ€. The aims of this study are to identify, describe the forms and pattern of greetings and leave-takings in English and Korea Language. This research uses a descriptive method, and Wardaugh and Fishmanâ€™s theories. The data in English were collected from books sociolinguistic, sourch internet, and the film The Best of Me. While the data in Korea languge were collected from the drama The Heirs. The result of this research shows that greetings and leave takings in English andÂ  Korean languageÂ  have two forms those are formal and informal. In addition, the writer finds that there three patterns in English and Korean language on greetings. Those patterns are the mutual formal greetings, the mutual informal greetings and the Non mutual greetings. The patterns of English leave-takings are the same as their greetings. On the other hand, Korean language has only two patterns of non mutual leave-takings formal and informal. Greetings and leave-takings in English and South Korean language have differences. For instance, greetings and leave-takings in English are various. Meanwhile inÂ  Korean language are limited. Â Â Keywords : Greetings and Leave-Takings English, South Korean language, Contrastive Analysis